błagam pomóżcie sam naj potrzebuje działania i rozwiązania błagam o pomoc!!
(-2)•6-(-3)
--------------- =
-9:(-3)

(-24):2+(-4)
--------------- =
-1•4

5:(-5)-0,2
-------------- =
-4•0,3

(-3)•(-5)+(-1)
----------------- =
8:(-4)




DAJE NAJJ


Odpowiedź :

Odpowiedź:

[tex]\frac{(-2)*6-(-3)}{-9:(-3)}=\frac{-12+3}{3}=\frac{-9}{3}=-3 \\\\\frac{(-24):2+(-4)}{-1*4}=\frac{-12-4}{-4}=\frac{-16}{-4}=4\\\\\\\frac{5:(-5)-0,2}{-4*0,3}=\frac{-1-0,2}{-1,2}=\frac{-1,2}{-1,2}=1\\\\\frac{(-3)*(-5)+(-1)}{8:(-4)}=\frac{15-1}{-2}=\frac{14}{-2}=-7[/tex]

Szczegółowe wyjaśnienie:

(-2)*6+3

———— = 5

(-9):(-3)

(-24):2+(-4)

—————— = 4

(-1)*4

5:(-5)-0,2 0,2

————— = ——— (nie jestem pewna)

(-4)*0,3 0,3

(-3)*(-5)+(-1)

—————— = 7

8:(-4)